p Pengaruh Pelatihan Dan Lingkungan Kerja Terhadap Kinerja Karyawan Yang Dimediasi Motivasi Pada PT. Telkom Witel Ridar - Novrizal, Dedy; Hendriani, Susi; Syapsan (Bahtera Inovasi, 2024)
Management is faced with the challenge of enhancing employee performance to ensure the company's survival in an unstable business environment. Telkom Witel Ridar needs to focus on improving employee performance and fostering innovation to develop and maintain superior resources. Employees are expected not only to enhance their performance but also to concentrate on optimal processes and outcomes. The higher the quality of employees, the better the task execution, leading to increased efficiency and effectiveness of the output. It is crucial for Telkom Witel Ridar's management to address these issues by providing effective training, enhancing management support, and fostering collaboration within the work environment to boost employee performance. This research aims to analyze and examine the influence of training (X1) and work environment (X2) on employee performance (Y) through motivation (Z) at PT. Telkom Witel Ridar. Enhancing employee productivity is considered to contribute to the company's growth. Data collection was conducted using a saturated sampling technique involving 55 employees, and data analysis was performed using PLS-SEM with the SmartPLS 4 application. The research findings indicate that (1) training has a negative and insignificant effect on employee performance; (2) training has a positive and insignificant effect on motivation; (3) the work environment has a negative and insignificant effect on employee performance; (4) the work environment has a positive and significant effect on motivation; (5) motivation has a positive and significant effect on employee performance; (6) training has a positive and insignificant effect on employee performance through motivation; and (7) the work environment has a positive and significant effect on employee performance through motivation. Based on the research results, it is recommended to provide additional training, mentoring, or other resources to help employees meet established standards, adjust training methods and content to be more relevant to employee needs, view training as a long-term investment in employee development, enhance managerial skills to optimize superior-subordinate relationships, and implement reward programs, regular positive feedback, or recognition opportunities in front of colleagues.